The Role of Destination Management Organizations in co-creating Local Territory Brand Identity, a comparative Analysis in Italy and Argentina - Coscarello, Mario; Ruffolo, Ida (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
This paper analyses how Destination Management Organizations (DMOs) contribute to the co-creation of a local territory brand identity. The aim of DMOs, which are organizational models for the management of tourist destinations apt to strengthen the services and resources of the various territorial identities, is to facilitate the collaboration and involvement of all actors in the area in order to increase the overall quality of tourism (Del Chiappa, Presenza, 2013; Coscarello, 2020). In particular, this paper presents the findings of an on-going comparative study on how DMOs in Italy and Argentina are managing their promotion and branding creating process for marketing campaigns. Specifically, the purpose of this article is to: (i) investigate how DMOs choose the content to create the destination identity, (ii) identify the roles of the various stakeholders in the process of place branding, and (iii) analyse the content and communication strategies used to promote the territory. This article contributes to the fast-growing place brand identity literature by exploring the role of DMOs in the co-creation of place-branding. It also intends to provide a better understanding of how effective the message is in contributing to their territorial brand identity. To the best of our knowledge, similar studies do not exist, therefore, it fills an important research gap. The research shows that the challenge for destinations seems to be the creation of a system network that, involving the public and private sectors, can take care of destination development. This may be the only way to implement a collaborative relationship and partnership with local, regional and national institutions for destination enhancement.